2008
DOI: 10.1007/s10450-008-9128-7
|View full text |Cite
|
Sign up to set email alerts
|

Capture of CO2 from flue gas streams with zeolite 13X by vacuum-pressure swing adsorption

Abstract: Vacuum swing adsorption (VSA) capture of CO 2 from flue gas streams is a promising technology for greenhouse gas mitigation. In this study we use a detailed, validated numerical model of the CO2VSA process to study the effect of a range of operating and design parameters on the system performance. The adsorbent used is 13X and a feed stream of 12% CO 2 and dry air is used to mimic flue gas. Feed pressures of 1.2 bar are used to minimize flue gas compression. A 9-step cycle with two equalisations and a 12-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(133 citation statements)
references
References 15 publications
3
129
1
Order By: Relevance
“…Many researchers around the world are 7 currently working on CO 2 capture from flue gases. It has been potentially demonstrated that CO 2 can be captured using PSA [224][225][226][227] but more fundamental and long-term pilot plant studies are required to properly benchmark this technique against amines. Also, olefin-paraffin separation by adsorption was quite studied, but the energetic consumption of the separation by adsorption is still comparable to distillation [228].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers around the world are 7 currently working on CO 2 capture from flue gases. It has been potentially demonstrated that CO 2 can be captured using PSA [224][225][226][227] but more fundamental and long-term pilot plant studies are required to properly benchmark this technique against amines. Also, olefin-paraffin separation by adsorption was quite studied, but the energetic consumption of the separation by adsorption is still comparable to distillation [228].…”
Section: Discussionmentioning
confidence: 99%
“…Throughput (mole/s m 3 ) = WC * B (1) where WC is the working capacity (moles/kg adsorbent/cycle), B is the bulk adsorbent density (kg adsorbent/m 3 ) and is the cycle time (s/cycle). Although structured adsorbents are developed with the aim of operation at faster cycle times (lower ), any development which simultaneously reduces adsorbent density ( B ) is detrimental to throughput.…”
Section: Volumetric Working Capacity and Adsorbent Loadingmentioning
confidence: 99%
“…The problem is especially acute for vacuum swing adsorption in which low vacuum pressures are needed for adsorbent regeneration, e.g. CO 2 VSA [1]. In this application, a vacuum pressure of 3 kPa may be needed to produce sufficient CO 2 recovery and throughput.…”
Section: Role Of Pressure Dropmentioning
confidence: 99%
“…Separation of carbon dioxide from flue gases [2], separation of gases (methane, carbon dioxide, hydrogen sulfide, water vapor) in the biogas technology [3], industrial drying of natural gas [4], purification and separation of complex mixtures [5], purification of wastewater containing heavy metals [6,7] have been investigated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%